PERANAN SISTEM INFORMASI AKUNTANSI TERHADAP KUALITAS SUMBER DAYA MANUSIA DAN PERSPEKTIF KEBERHASILAN PENERAPAN ERP PADA PT TELKOM INDONESIA - Rulis Setyowati; Hwihanus Hwihanus (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Enterprise Resource Planning (ERP) systems integrate all organizational functions, integrating inventory management, manufacturing, finance, human resources and accounting into one system. modular ERP systems for businesses can afford any module to suit their specific needs. ERP enables sharing of information between various business functions and improves communication with external parties. One use of the system is called